2019
DOI: 10.1007/s10709-019-00055-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the grapevine genotypes of the Russian Vitis ampelographic collection using iPBS markers

Abstract: Cultivated grapevine (Vitis vinifera L. ssp. sativa D.C.) is one of the oldest agricultural crops, each variety comprising an array of clones obtained by vegetative propagation from a selected vine grown from a single seedling. Most clones within a variety are identical, but some show a different form of accession, giving rise to new divergent phenotypes. Understanding the associations among the genotypes within a variety is crucial to efficient management and effective grapevine improvement. Inter-primer bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…The main diversity in the iPBS profile arose from Alternaria alternata isolates (160 polymorphic bands out of 198), which was the most abundant species among the isolates (15 out of 25). Notably, the level of detectable polymorphism detected in our study is lower than that reported in similar studies using the iPBS method on both plants (Doungous et al, 2015;Doungous et al, 2020) and other fungi species (Milovanov et al, 2019;Monden, Yamaguchi & Tahara, 2014;Teo et al, 2005;Vukich et al, 2009). The amplified PCR products ranged from 200 to 3000 bp and had on average 10-30 bands per isolate.…”
Section: Genetic Diversity Among Alternaria Spcontrasting
confidence: 80%
See 2 more Smart Citations
“…The main diversity in the iPBS profile arose from Alternaria alternata isolates (160 polymorphic bands out of 198), which was the most abundant species among the isolates (15 out of 25). Notably, the level of detectable polymorphism detected in our study is lower than that reported in similar studies using the iPBS method on both plants (Doungous et al, 2015;Doungous et al, 2020) and other fungi species (Milovanov et al, 2019;Monden, Yamaguchi & Tahara, 2014;Teo et al, 2005;Vukich et al, 2009). The amplified PCR products ranged from 200 to 3000 bp and had on average 10-30 bands per isolate.…”
Section: Genetic Diversity Among Alternaria Spcontrasting
confidence: 80%
“…In this regard, the iPBS method developed by Kalendar et al (2010) has advantages for applications in the evaluation of genetic diversity, because it allows direct detection of polymorphism regardless of the eukaryotic species. It is particularly beneficial when detecting genetic diversity among fungi isolates; since it can detect polymorphisms in many anonymous loci across the genome simultaneously, it is a highly effective method for studying clonal variability (Doungous et al, 2020;Kalendar et al, 2010;Milovanov et al, 2019). Moreover, since most of the retrotransposons are often mixed with each other, the PCR process amplifies many products because the primers are designed to target conserved regions of retrovirus and LTR retrotransposon primer binding sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers complementary to interspersed repeats allow amplification of the region between these repeats if the distance between the repeats does not exceed the processivity of the used DNA polymerases (Kalendar et al, 2019). Therefore, this approach, based on PCR between interspersed repeats and mobile genetic elements, can be easily adapted for any eukaryotic species for the rapid detection of molecular genetic polymorphisms even in an agarose gel (Doungous et al, 2019;Hosid et al, 2012;Kalendar, Amenov & Daniyarov, 2018;Kalendar & Schulman, 2013;Milovanov et al, 2019;Turzhanova et al, 2020). Thus, application of PCR methods based on the use of conserved sequences of interspersed repeats and mobile genetic elements allows universal and efficient detection of polymorphisms for almost every eukaryotic species (Kalendar, Amenov & Daniyarov, 2018;Smykal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The stability of retrotransposon integration sites and recombination events allows them to be used as molecular genetic markers in genetic map construction [28][29][30][31][32]. Retrotransposon markers have also been widely used to assess genetic diversity in many species [33][34][35][36][37][38][39]. Given that plant retrotransposons are stressactivated [15,40], their role in generating ecogeographical patterns of genomic diversity is of particular interest.…”
Section: Introductionmentioning
confidence: 99%